Perceptual Tuning Influences Rule Generalization: Testing Humans With Monkey-Tailored Stimuli. (April 2019) - Ravignani, Andrea; Filippi, Piera; Tecumseh Fitch, W.
Comparative research investigating how nonhuman animals generalize patterns of auditory stimuli often uses sequences of human speech syllables and reports limited generalization abilities in animals. Here, we reverse this logic, testing humans with stimulus sequences tailored to squirrel monkeys. When test stimuli are familiar (human voices), humans succeed in two types of generalization. However, when the same structural rule is instantiated over unfamiliar but perceivable sounds within squirrel monkeys' optimal hearing frequency range, human participants master only one type of generalization. These findings have methodological implications for the design of comparative experiments, which should be fair towards all tested species' proclivities and limitations.